PENGARUH MODEL PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PAI SISWA KELAS VII SMP NEGERI 1 KABANJAHE KABUPATEN KARO - Sahimin Min (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This research aims to know the 1) The learning outcomes of students taught withIslamic Studies model learning Problem Based Learning is higher than the results of the learningof students who are taught with the conventional learning model, 2) The results of learningIslamic Studies students who have a visual learning style that is taught by learning modelof Problem Based Learning is higher than the results of a study of students who have a kinestheticlearning style, 3) The results of learning Islamic Studies students who have a visuallearning style taught by conventional learning model is higher than the results of a study ofIslamic Studies students who have learning style kinesthetic, 4) the influence between themodel of learning and learning style against the results of student learning in Islamic studies.The population in this research is the entire class VII students of SMP Negeri 1 Kabanjahe aMuslim amounted to 90 people. Sample withdrawal technique used was random samplingtechniques. Sample research amounted to 60 students of which 30 students as a group experimentthat taught with Problem Based Learning and 30 students as a group with the conventionallearning model. Research methods used are factorial experimental design with all 2 x 2.Data analysis technique used is the test of ANAVA two lines on the significant extent of á =0.05. The results of this research is 1) student learning outcomes that are taught with a modellearning Problem Based Learning higher than students taught with the conventional value oflearning model fh 16.68 Ã ft 3.99 on significant level á = 0.05, 2) learning outcome of studentswith a visual learning style is higher compared to the results of a study of Islamic Studiesstudents with kinaesthetic learning style with a value of fh 15.30 Ã ft 3.99 on significant levelá = 0.05, 3) the results of a study of students who have a visual learning style taught byProblem Based Learning is more tingggi compared to students who have a kinesthetic learningstyle with a value of fh 7.889 Ã ft 3.980 at significant levels á = 0.05, 4) There are influencesbetween the use of a model of learning and learning style against the results of the studyof Islamic Studies students with value fh 4.25 > ft = 3.99.